2015
DOI: 10.5194/nhess-15-1617-2015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic sensitivity of flood runoff and inundation: 2011 Thailand floods in the Chao Phraya River basin

Abstract: Abstract. The Thailand floods in 2011 caused unprecedented economic damage in the Chao Phraya River basin. To diagnose the flood hazard characteristics, this study analyses the hydrologic sensitivity of flood runoff and inundation to rainfall. The motivation is to address why the seemingly insignificant monsoon rainfall, or 1.2 times more rainfall than for past large floods, including the ones in 1995 and 2006, resulted in such devastating flooding. To quantify the hydrologic sensitivity, this study simulated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 25 publications
4
43
1
1
Order By: Relevance
“…Based on Mateo et al (2014), the Manning's coefficient was fixed at 0.024 in the river channel and 0.10 in the floodplain for the entire basin. These values of Manning's coefficient are comparable with those used in other studies in the Chao Phraya River Basin (Visutimeteegorn et al, 2007;Keokhumcheng et al, 2012;Sayama et al, 2015) and those obtained by USGS from lab and field data (Aldridge and Garrett, 1973). By using the calibrated parameters, CaMa-Flood can adequately simulate the discharge and flood inundation in the basin ( Fig.…”
Section: Model Calibration and Validationsupporting
confidence: 88%
“…Based on Mateo et al (2014), the Manning's coefficient was fixed at 0.024 in the river channel and 0.10 in the floodplain for the entire basin. These values of Manning's coefficient are comparable with those used in other studies in the Chao Phraya River Basin (Visutimeteegorn et al, 2007;Keokhumcheng et al, 2012;Sayama et al, 2015) and those obtained by USGS from lab and field data (Aldridge and Garrett, 1973). By using the calibrated parameters, CaMa-Flood can adequately simulate the discharge and flood inundation in the basin ( Fig.…”
Section: Model Calibration and Validationsupporting
confidence: 88%
“…The apparent increase in the streamflow in the increasing trend of the precipitation scenarios could lead to flooding events during the wet season. Monsoonal rains occur in the Chao Phraya River every year from May to October, making the watershed vulnerable to flood-related disasters during this season [93][94][95]. In this study, the streamflow increased in May and continued to rise until reaching their peak in September.…”
Section: Precipitationmentioning
confidence: 71%
“…The model deals with slopes and river channels separately [26,54]. At a grid cell, in which a river channel is located, the model assumes that both the slope and river are positioned within the same grid cell.…”
Section: Rri Modelmentioning
confidence: 99%
“…The RRI model setup and its equations are explained in Sayama [26,54]. The various applications of the RRI model in hydrological studies can be found in several studies [26,41,54,58,59]. The model equations are derived based on the following mass balance Equation (1) and momentum Equations (2) and (3) for gradually varied unsteady flow:…”
Section: Rri Modelmentioning
confidence: 99%